Attitudes of Students of the Faculty of Education in Al-Qarah Buli toward Psychotherapy and Their Relationship with Some Demographic Variables: A Field Study - Ruqayah Mohammed Abdulsalam Aljadi (Journal of Libyan Academy Bani Walid, 2026)
This study aimed to identify the attitudes of students of the Faculty of Education in Al-Qarah Buli toward psychotherapy, and to examine whether there were statistically significant differences in these attitudes according to the variables of gender, age, and academic year. The study adopted the descriptive analytical method and used a questionnaire as a tool for data collection. The questionnaire was administered to a sample of 50 male and female students from the Faculty of Education in Al-Qarah Buli. The results showed that the sample members had generally positive attitudes toward the importance of psychotherapy, as most students acknowledged its role in improving quality of life, enhancing self-understanding, and helping individuals face their psychological and emotional problems. The results also indicated that there were no statistically significant differences in students’ attitudes toward psychotherapy attributable to gender, age, or academic year. However, the study revealed the persistence of some aspects of social stigma and cultural reservations toward psychotherapy, such as fear of its impact on reputation, the sensitivity of discussing it within society, and the tendency of some members of society to associate mental illness with magic or possession by jinn. In light of these results, the study recommended the need to promote psychological awareness within educational institutions, and to organize awareness seminars and lectures that contribute to correcting misconceptions about psychotherapy and encouraging students to seek psychological help when needed without fear or embarrassment.